2013
DOI: 10.1080/17470218.2013.828314
|View full text |Cite
|
Sign up to set email alerts
|

Raven's Matrices and Working Memory: A Dual-Task Approach

Abstract: Raven's Matrices Test was developed as a "pure" measure of Spearman's concept of general intelligence, g. Subsequent research has attempted to specify the processes underpinning performance, some relating it to the concept of working memory and proposing a crucial role for the central executive, with the nature of other components currently unclear. Up to this point, virtually all work has been based on correlational analysis of number of correct solutions, sometimes related to possible strategies. We explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
1
23
3
Order By: Relevance
“…These findings are unexpected because articulatory suppression is beneficial for both groups, whereas we had expected that it would increase response times. This result is not consistent with other studies, which found either no effect or a detrimental effect of articulatory suppression on reasoning tasks involving analogies (Rao & Baddeley, 2013;Waltz et al, 2000). Thus, this data seems difficult to interpret.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are unexpected because articulatory suppression is beneficial for both groups, whereas we had expected that it would increase response times. This result is not consistent with other studies, which found either no effect or a detrimental effect of articulatory suppression on reasoning tasks involving analogies (Rao & Baddeley, 2013;Waltz et al, 2000). Thus, this data seems difficult to interpret.…”
Section: Discussioncontrasting
confidence: 99%
“…These individual differences appear to relate to variation in verbal and spatial working memory skills, but do not necessarily translate into differences in reasoning skill ( Bacon, Handley, & Newstead, 2005 ). Similarly, matrix reasoning tasks, which predominantly consist of visuospatial stimuli but which can be solved using various visual or verbal strategies, do not appear to be specifically affected by articulatory suppression: for instance, Rao and Baddeley (2013) compared effects of number repetition (articulatory suppression) and backward counting (central executive interference) on matrix reasoning, and found that only the latter negatively affected the time it took to reach a solution. Thus, inner speech does not appear necessary for tasks involving logical reasoning, even for verbal material.…”
Section: Inner Speech In Adult Cognitionmentioning
confidence: 99%
“…In addition to these correlational studies there are results from an experimental study suggesting that overloading working memory while performing a matrix reasoning test affected performance in the reasoning measure (Rao & Baddeley, 2013). In detail, participants were asked to remember a set of three digits and count backwards while working on the matrix reasoning task.…”
Section: The Relationship Of Working Memory Capacity With Intelligencementioning
confidence: 99%